Synergistic effects of ISL1 and KDM6B on non-alcoholic fatty liver disease through the regulation of SNAI1 - Fei Zhao; Jinjing Ke; Wensheng Pan; Hanghai Pan; Miao Shen (BMC, 2022)
Abstract Background The increasing incidence of non-alcoholic fatty liver disease (NAFLD) has been reported worldwide, which urges understanding of its pathogenesis and development of more effective therapeutical methods for this chronic disease. In this study, we aimed to investigate the effects of a LIM homeodomain transcription factor, islet1 (ISL1) on NAFLD. Methods Male C57BL/6J mice were fed with a diet high in fat content to produce NAFLD models. These models were then treated with overexpressed ISL1 (oe-ISL1), oe-Lysine-specific demethylase 6B (KDM6B), oe-SNAI1, or short hairpin RNA against SNAI1. We assessed triglyceride and cholesterol contents in the plasma and liver tissues and determined the expressions of ISL1, KDM6B and SNAI1 in liver tissues. Moreover, the in vitro model of lipid accumulation was constructed using fatty acids to explore the in vitro effect of ISL1/KDM6B/SNAI1 in NAFLD. Results The results showed that the expressions of ISL1, KDM6B, and SNAI1 where decreased, but contents of triglyceride and cholesterol increased in mice exposed to high-fat diet. ISL1 inhibited lipogenesis and promoted lipolysis and exhibited a synergizing effect with KDM6B to upregulate the expression of SNAI1. Moreover, both KDM6B and SNAI1 could inhibit lipogenesis and induce lipolysis. Importantly, the therapeutic effects of ISL1 on in vitro model of lipid accumulations was also confirmed through the modulation of KDM6B and SNAI1. Conclusions Taken together, these findings highlighted that ISL1 effectively ameliorated NAFLD by inducing the expressions of KDM6B and SNAI1, which might be a promising drug for the treatment of NAFLD.